The Influence of Economic Growth To Poverty and Its Relation To The Pro Poor In Indonesia - Ali Attibrizi; Khusnul Ashar; Devanto Shasta Pratomo (e-2477-1929)
This research aims to examine the extent to which Indonesia is able to carry out pro poor growth. To solve this problem, the authors use Pro Poor Growth Index as an analysis tool. The results show that during 2004-2013, economic growth in Indonesia is pro-poor so that the benefits of economic growth can be felt throughout society. Another objective of this research was to determine the effect of economic growth on poverty in Indonesia, both directly and indirectly. In the indirect effects, economic growth will affect intermediary aspects. These aspects consist of inequality, human development, and unemployment. The author used path analysis as an analysis tool. The results showed that human development is the most influential intermediary aspect on the relationship between economic growth and poverty so that the government has to increase the education, health, and purchasing power aspects so that the poverty rate decreased faster.Keywords: pro-poor growth, economic growth, inequality of income distribution, human development, unemployment, poverty, path analysis